Real‐time quality authentication of honey using atmospheric pressure chemical ionisation mass spectrometry (APCI‐MS). (29th May 2019) - ElMasry, Gamal; Morsy, Noha; Al‐Rejaie, Salim; Ayed, Charfedinne; Linforth, Robert; Fisk, Ian
Summary: The aim of this study was to use gas chromatography‐mass spectrometry (GC‐MS) and APCI‐MS techniques to detect adulteration in honey. The key volatile compounds in the headspace of the adulterated honey were marked by GC‐MS and their representative fragment ions were utilised in scanning honey samples using the real‐time APCI‐MS system. The PLS models validated using independent data sets resulted in coefficient of the determination ( R p 2 ) of 0.97 and 0.96 and root mean square error in prediction (RMSEP) of 2.62 and 2.45 for the GC‐MS and APCI‐MS data sets respectively. The most efficient volatiles from GC‐MS analysis and their corresponding fragment ions m/z from APCI‐MS data analysis were then identified and used to develop new PLS models to predict the level of adulteration. The best PLS model gave R p 2 of 0.95 and RMEP of 2.60% in the independent validation set indicating that the model was very accurate in predicting the level of adulteration. Abstract : The suggested method detailed in this article could be directly used to recognise the identity of the honey and the presence of unexpected compounds in honey such as sugar syrups. In essence, the ideal scenario should start first by identifying the key volatile compounds using GC‐MS system and then utilize their corresponding fragment ions in selected‐ion mode for real‐time analysis on the APCI‐MS system.